Measurement characteristics of WHODAS 2.0 and WHODAS-Child: a systematic review of global psychometric studies in specific populations since 2010 - Federici, Stefano; Tosti, Alessandro; Russo, Elena A.; Conigli, Lorenzo (Frontiers in Psychiatry, 2026)
IntroductionThis global systematic review evaluated the psychometric properties, namely the reliability and validity, of all WHODAS 2.0 versions and forms, including WHODAS-Child, which has been used in specific populations since 2010, in assessing alignment with the WHO manual.Materials and methodsFollowing PRISMA-COSMIN guideline, electronic databases and a curated personal library were searched up to April 30, 2025. Included were 143 empirical studies on WHODAS 2.0 and WHODAS-Child in samples with specific populations, spanning 43 countries.ResultsAcross five data extraction forms, the mean and median values of the aggregated data regarding the measurement characteristics of WHODAS 2.0 and WHODAS-Child are reported. The 36-item version demonstrated excellent internal consistency (mean α = 0.92), while the 12-item one showed good reliability (mean α = 0.88), and the test-retest reliability was strong for both (ICC = 0.89–0.91). Factor analyses supported the six-domain structure for the 36-item version and WHODAS-Child, though more variability was noted for the 12-item version. Cultural and age-related challenges emerged, indicating the need for contextual adaptations.Discussion and conclusionsThe results showed good behavior of WHODAS 2.0, albeit slightly lower than the psychometric profiles described in the Manual. WHODAS-Child, though promising, requires further validation and refinement, particularly for cross-cultural applications.